Industrial Heat Pump-Assisted Wood Drying - Minea, Vasile; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
This book discusses conventional as well as unconventional wood drying technologies. It covers fundamental thermophysical and energetic aspects and integrates two complex thermodynamic systems, conventional kilns and heat pumps, aimed at improving the energy performance of dryers and the final quality of dried lumber. It discusses advanced components, kiln energy requirements, modeling, and software and emphasizes dryer/heat pump optimum coupling, control, and energy efficiency. Problems are included in most chapters as practical, numerical examples for process and system/components calculation and design. The book presents promising advancements and R&D challenges and future requirements.
1. Introduction -- 2. Wood -- 3. Moisture in Wood -- 4. Moist Air -- 5. Importance of Wood Drying -- 6. Wood Drying Methods -- 7. Mechanisms of Lumber Drying -- 8. Kiln-Wide Lumber Drying -- 9. Heat Pump-Assisted Wood Dryers -- 10. Heat Pump Systems for Drying -- 11. Refrigerants -- 12. Heat Exchangers without Phase Changes -- 13. Moisture Condensers -- 14. Refrigerant-to-Air Condensers -- 15. Heat Pump Modeling -- 16. Case Studies -- 17. Present and Future R&D Challenges.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Construction / Heating, Ventilation & Air Conditioning; TECHNOLOGY & ENGINEERING / Manufacturing; Lumber -- Drying -- Equipment and supplies; Heat pumps; Electronic books